THERMOCLINE WATER TEMPERATURE GRADIENT AT THE INDONESIAN THROUGHFLOW PATHWAYS DURING LAST GLACIAL MAXIMUM (LGM) - Rachmayani, Rima; Larasati, Oktavira Dwi Demia; Hendrizan, Marfasran (BULLETIN OF THE MARINE GEOLOGY, 2025)
This study aims to investigate the strength of the Indonesian Throughflow (ITF) during the Last Glacial Maximum (LGM) in comparison to the Pre-Industrial (PI) at the Makassar Strait, the Molucca Sea, and the Banda Sea, representing the pathways of the ITF. The analysis was performed based on the temperature distribution of the south (S) and north (N) thermocline gradients. Temperature data were obtained from the simulation of the Climate Community System Model, version 4 (CCSM4). The depth of the thermocline layer during the LGM and the PI period exhibits seasonal variability across the S-N stations. At Station 1, 2, and 3, the thermocline depth during the LGM ranges from 49 - 218 m (51 - 251 m), 55 - 250 m (69 - 254 m), and 48 - 238 m (48 - 218 m) in the south (north), respectively. The analysis of seasonal temperature variations in the thermocline layer in the three locations indicates that the ITF was significantly weakened both during the LGM and PI, indicated by the negative S-N Thermocline Water Temperature (TWT) gradient. The result suggests the southern part of each station is predominantly fresher compared to the northern part during these times. Additionally, it implies that the ITF is more robust in the eastern region (Banda Sea) during the LGM compared to the PI. This variation may relate to the intensity of seasonal local winds, mixing processes, and the remote influence of El Niño-like events, which could affect water transport along the pathway of the ITF.